INTERAKSI GURU DAN MURID DALAM PERSPEKTIF AL-QUR’AN: SUATU THEMATIC EXEGESIS ATAS QS. ALKAHFI [18]: 60-82 - Maulana, Muhammad Rifkhi; Akmansyah, Muhammad; Fathoni, A.; Amiruddin, Amiruddin (LPPM STAI Ihyaul Ulum Gresik, 2026)
This study analyzes the concept of interaction between teachers and students from the perspective of the Qur'an through a thematic exegesis of QS. Al-Kahf [18]: 60–82, which tells the story of the meeting of the Prophet Moses and Khidr. The purpose of this study is to identify pedagogical values ​​that represent the educational relationship of the Qur'an and its relevance to the paradigm of contemporary Islamic education. The approach used is a qualitative literature study based on primary sources of classical and contemporary interpretations, as well as the latest research in the field of Islamic education. The analysis was conducted using content analysis techniques to identify the main themes in the interaction between Moses and Khidr. The results of the study show that the relationship between teachers and students in the story displays three main values ​​from the student's perspective, namely tawadhu' (humility), sabar (steadfastness in learning), and taat (obedience to the teacher's guidance). From the teacher's perspective, the principles of hikmah (wisdom), tadarruj (gradual method), and amanah ilmu (ethics in conveying knowledge) were found. These values ​​form a framework for Qur'anic pedagogy that balances the cognitive, affective, and spiritual dimensions in the learning process. Research findings also indicate that the story of Moses and Khidr is relevant to modern pedagogical concepts such as mentoring models, experiential learning, and scaffolding within the zone of proximal development (ZPD). The interaction between the two emphasizes that education, from a Qur'anic perspective, is not merely the transfer of knowledge but rather the process of developing wisdom, character, and etiquette. Thus, Surah Al-Kahf (18:60–82) can be used as a conceptual model for Islamic education based on Qur'anic values, oriented toward the formation of intellectually intelligent, spiritually mature, and socially noble human beings.